WOMEN IN MEDICINE, Dr. Juan Riera Palmero, Editorial de los Anales 2019. (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2023)
Currently gender studies have multiplied, being a new line of research, sociological, anthropological, historical and legislative with a deep political dimension. The volume of publications, books, monographs and specialized magazines on the history of women is growing.
Keywords: Woman; Medicine; Feminism